An innovative alkaline protease-based pretreatment approach for enhanced short-chain fatty acids production via a short-term anaerobic fermentation of waste activated sludge. (September 2020) - Pang, Heliang; Pan, Xinlei; Li, Lin; He, Junguo; Zheng, Yanshi; Qu, Fangshu; Ma, Yingqun; Cui, Baihui; Nan, Jun; Liu, Yu
Graphical abstract: Highlights: Noticeable SCOD of 5363.7 mg/L was achievable with AP-based pretreatment at pH 10. Sludge disintegration and cell lysis induced biodegradable organic matter release. AP pretreatment improved hydrolase activities and accelerated fermentation process. SCFAs yield reached 607 mg COD/g VSS by short-term anaerobic fermentation (3 days). Detailed mechanism, engineering implications and economic benefits were proposed. Abstract: This study reported a novel pretreatment approach with combination of alkaline protease (AP) and pH 10 for enhancing short-chain fatty acids (SCFAs) production from waste activated sludge (WAS). Through the AP-based pretreatment, WAS flocs were disintegrated with cell lysis, leading to release of biodegradable organic matters. At the external AP dosage of 5%, SCOD of 5363.7 mg/L (SCOD/TCOD = 32.5%) was achievable after 2-h pretreatment. More than 66% of SCOD was composed of proteins and carbohydrates. Considerable SCFAs of 607 mg COD/g VSS was produced over a short-term anaerobic fermentation of 3 days, which was 5.4 times higher than that in the control. Acetic and propionic acids accounted for 74.1% of the SCFAs. The AP-based approach increased endogenous protease and α-glucosidase activities, facilitating biodegradation of dissolved organic matters and SCFAs production. Such approach is promising for WAS disposal and carbon recovery, the produced SCFAs might supply 60% of carbon gap in wastewater.